The Effect of Sporulation Medium on Alicyclobacillus Acidoterrestris Guaiacol Production in Apple Juice - Molva, Çelenk; Baysal, Ayşe Handan; Baysal, Ayşe Handan; Molva, Çelenk (Academic Press Inc., 2016)
The present study evaluated the effect of sporulation medium on guaiacol formation from vanillin and vanillic acid by Alicyclobacillus acidoterrestris DSM 3922 in the reconstituted apple juice (pH 3.82, °Brix 11.3). For sporulation, potato dextrose agar and Bacillus acidoterrestris agar were used. After heat-activation, spores were turned into vegetative cells and inoculated into juice samples to a final concentration of 103 or 105 CFU/mL. Samples were incubated at 37 °C for 264 h and guaiacol concentration was determined using peroxidase enzyme colourimetric assay. Based on the results, the conversion of vanillic acid into guaiacol was faster than that of vanillin among both cell suspensions. Also, there were no significant differences among any of the samples inoculated into apple juice spiked with vanillin at the end of the incubation period (P > 0.05). In the case of vanillic acid, the guaiacol concentrations were significantly different among cells activated from spores produced on PDA and BATA (P < 0.05). The obtained results suggested that type of sporulation medium composition may affect the guaiacol concentration depending on inoculum level and type of precursor present in the apple juice.
Keywords: Guaiacol; Juice spoilage; Sporulation medium; Vanillic acid; Vanillin